2022
DOI: 10.1017/wsc.2022.46
|View full text |Cite
|
Sign up to set email alerts
|

Dicamba residue persistence in processing tomato

Abstract: There is zero tolerance for dicamba and dicamba metabolite residue in tomato (Solanum lycopersicum L.) fruit following exposure to dicamba. Field trials were conducted in 2020 and 2021 to determine the persistence of dicamba and metabolite [5-hydroxy dicamba and 3,6-dichlorosalicylic acid (DCSA)] residue in processing tomato shoots and fruits. Dicamba was applied 49 days after transplanting at 0, 0.53, 5.3, and 53 g ae ha−1. Tomato plants were harvested 5, 10, 20, 40, and 61 days after treatment (DAT). No 5-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The most common plant symptoms under the effects of these herbicides are epinasty, stem and branch curvature, and growth arrest with meristem chlorosis, followed by necrosis [19,20]. Our results obtained in this study are consistent with those found by Meyers et al [21], where dicamba drift negatively affected tomato plants and compromised fruit productivity. In addition, Warmund et al [4] reported that tomato cultivars treated with herbicide 2,4-D and dicamba can produce less total and marketable yield than their respective non-treated control.…”
Section: Discussionsupporting
confidence: 92%
“…The most common plant symptoms under the effects of these herbicides are epinasty, stem and branch curvature, and growth arrest with meristem chlorosis, followed by necrosis [19,20]. Our results obtained in this study are consistent with those found by Meyers et al [21], where dicamba drift negatively affected tomato plants and compromised fruit productivity. In addition, Warmund et al [4] reported that tomato cultivars treated with herbicide 2,4-D and dicamba can produce less total and marketable yield than their respective non-treated control.…”
Section: Discussionsupporting
confidence: 92%
“…Soybean injury in response to florpyrauxifen-benzyl was detectable at a distance farther from a drift source than was detectable in spray deposits (Butts et al 2022). In experiments with processing tomatoes, dicamba and dicamba residues from applications of 1/100X and 1/1,000X rates were detectable only in shoot tissues on the day of exposure (Meyers et al 2022). However, the dicamba residues were more persistent in tomato fruit, indicating the potential for crop rejection at the market, based on agricultural regulations (U.S. Code of Federal Regulations 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The potential for dicamba exposure on crops has been well characterized, whether through herbicide drift, volatilization, or sprayer contamination (Behrens and Lueschen 1979; Egan et al 2014; Inman et al 2021). Specialty crops are especially impacted by off-target movement of dicamba due to their high value and the potential for dicamba residues to make crops like tobacco ( Nicotiana tabacum L.) and tomato ( Solanum lycopersicum L.) unmarketable (Inman et al 2021; Meyers et al 2022). The effects of dicamba exposure have been assessed extensively in annual specialty crop systems, including crops of the Brassicaceae, Convolvulaceae, Cucurbitaceae, Fabaceae, Ipomoaceae, and Solanaceae families (Culpepper et al 2018; Hand et al 2020; Inman et al 2021; Mohseni-Moghadam and Doohan 2015; Shankle et al 2021; Wasacz et al 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean (Glycine max (L.) Merr.) [7,17,18] Rice (Oryza sativa L.) [19] Cotton (Gossypium hirsutum L.) [20] Peanut (Arachis hypogaea L.) [21] Tomato (Solanum lycopersicum L.) [18,22,23] Lettuce (Lactuca sativa L.) [18] Pumpkin (Cucurbita maxima Duch) [18] Oilseed rape (Brassica napus L.) [18] Pepper (Capsicum annuum L.) [18] Sunflower (Helianthus annuus L.) [18] Cucumber (Cucumis sativus L.) [7] Eggplant (Solanum melongena L.) [7] Snap bean (Phaseolus vulgaris L.) [7] Potato (Solanum tuberosum L.) [24] Sweetpotato (Ipomoea batatas (L.) Lam.) [25] Mandarin (Citrus reticulata) [26] Grapevine (Vitis vinifera L.) [27] Brazilian peppertree (Schimus terebinthifolius Raddi.)…”
Section: Crop Referencementioning
confidence: 99%